SIMBOL DAN PROSES KOMUNIKASI TOKOH ADAT TERHADAP BUDAYA EKAH SUKU SUNDA - Hera Ovnavia (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
AbstractHera Ovnavia. C1D1 12 171. Symbols and Communication Process Indigenous Leader to Culture Ekah Sundanese (Studies Ethnography of Communication at the Sundanese society in the Village Atula , District Ladongi , East Kolaka Timur) supervising I Masrul, S.Ag., M.Si and supervising II by Joko, S.Sos, M.Si The Problems in this study Any communication symbol contained in a ceremony ekah ( Aqiqah ) and how the communication process of traditional leaders about ekah ( Aqiqah ) in maintaining Sundanese culture in Sub atula Eastern District of Kolaka Ladongi, The purpose of this study was to determine the communication symbol contained in ekah ceremony and traditional leaders about the communication process ekah in maintaining Sundanese culture, The benefits of this research are theoretically : this study is expected to add to and expand the horizons of the theory ethnography of communication , practical : this study is expected to provide input to the community that will become traditional leaders to maintain the original culture Sundanese , methodologically : for further research , it can be used as one of the reference materials and reference in conducting research in connection with symbols and communication processes ekah traditional leaders against ethnic Sundanese culture.Subjects in this study were traditional leaders and community leaders who know clearly about the ceremony ekah Sundanese . Mechanical determination of informants in this study be done by purposive sampling technique which is chosen deliberately by considering that the informant in question know and memehami true heart of the problem , with the number of informants as many as seven people . The data collected was analyzed using analysis of ethnography of communication . These results indicate that the symbols contained in the ceremony ekah include symbols verbal embodied in the form of nadoman and non - verbal embodied in the form of property or objects contained therein while the communication process custom figure includes the primary communication are realized in the form of delivering a message to his family and the secondary process manifested in the form of delivering a message to the community that the ceremony ekah Sundanese conserved and respect and preserve Sundanese heritage.Keywords: Symbol Of Communication , Communication Process , Sundanese traditional figure , Ekah Culture Sundanese.